2014
DOI: 10.2478/s11534-014-0520-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spontaneously generated coherence on atom-photon entanglement in a Λ-type system with an incoherent pump

Abstract: Abstract:Owing to interference induced by spontaneous emission, the density-matrix equations in a three-level Λ-type system have an additional coherence term, which plays a critical role in modulating the inversionless gain and electromagnetically induced transparency effect. In addition, it is shown that spontaneously generated coherence (SGC) has an effect on the entanglement between an atom and a photon of the coupling laser field by calculating the degree of entanglement (DEM) of the atomic system. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In this way, the control and manipulation of the decoherence can be exploited to enhance the entanglement between the system and its environment. It is proven that the entanglement of the induced steady state between a two-level atom and its spontaneous emission excitation is manipulated by detuning the intensity and relative phase of the fields [ 49 , 50 , 51 , 52 , 53 , 54 ]. It is worth noting that the hybrid entanglement between a photon and an atom has applications in quantum tools, such as quantum networks [ 55 ], quantum repeater [ 56 , 57 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the control and manipulation of the decoherence can be exploited to enhance the entanglement between the system and its environment. It is proven that the entanglement of the induced steady state between a two-level atom and its spontaneous emission excitation is manipulated by detuning the intensity and relative phase of the fields [ 49 , 50 , 51 , 52 , 53 , 54 ]. It is worth noting that the hybrid entanglement between a photon and an atom has applications in quantum tools, such as quantum networks [ 55 ], quantum repeater [ 56 , 57 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, manipulation and control of decoherence can lead to harnessing system-environment entanglement. It has been demonstrated that the induced steady state entanglement between an atom and its spontaneous emission excitation can be controlled by intensity, detuning and relative phase of applied fields [21][22][23][24][25][26]. It is noteworthy that hybrid atom-photon entanglement has found applications in new quantum tools such as quantum repeater [27,28], quantum networks and quantum memories [29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the context of semi-classical theory of atom-light interaction, it has been shown that the induced steady state entanglement between an atom and its spontaneous emission can be controlled by intensity and detuning parameter of an applied field [23]. It has, also, been demonstrated that the atom-photon entanglement depends on the relative phase of applied fields [24,25] and incoherent driving pump field [26].…”
Section: Introductionmentioning
confidence: 99%